Directive (EU) 2019/633 on unfair commercial practices for a more sustainable agricultural and food supply chain - Sánchez Hernández, Ángel (Przegląd Prawa Rolnego, 2020)
Generally, in all commercial negotiations in the agricultural and food supply chain, the bargaining power enforces reduced prices and an imposition of unfair contractual conditions which suppliers have to accept to avoid being excluded from the market. Contractual conditions that harm the weaker party with less negotiating power and no possibility of withdrawing from the commercial relationship, imposed by a party in a privileged position, are described as unfair commercial practices. What is more, they are not only detrimental to agri-food businesses, but also to consumers and the overall functioning of the market. The uneven bargaining power between buyers and suppliers in the agricultural and food supply chain, leading to commercial relationships lacking clarity, transparency and fairness may effectively proper functioning of the market.